2010
DOI: 10.1002/chem.200902891
|View full text |Cite
|
Sign up to set email alerts
|

A Time‐Resolved Spectroscopic Study of the Bichromophoric Phototrigger 3′,5′‐Dimethoxybenzoin Diethyl Phosphate: Interaction Between the Two Chromophores Determines the Reaction Pathway

Abstract: 3',5'-Dimethoxybenzoin (DMB) is a bichromophoric system that has widespread application as a highly efficient photoremovable protecting group (PRPG) for the release of diverse functional groups. The photodeprotection of DMB phototriggers is remarkably clean, and is accompanied by the formation of a biologically benign cyclization product, 3',5'-dimethoxybenzofuran (DMBF). The underlying mechanism of the DMB deprotection and cyclization has, however, until now remained unclear. Femtosecond transient absorption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 85 publications
3
26
1
Order By: Relevance
“…Our results for compound 1 are consistent with the formation of its triplet excited state and the comparable cationic species A . A recent study on the 3′,5′‐dimethoxybenzoin photocage suggested that the photochemical pathway involving this cyclohexadienyl cation structure played only a minor role and a faster process could be the predominant pathway 52. Due to the limitations of our equipment, we were not able to observe any other intermediates prior to generating the proposed cyclohexadienyl cation structure ( A ).…”
Section: Methodsmentioning
confidence: 78%
“…Our results for compound 1 are consistent with the formation of its triplet excited state and the comparable cationic species A . A recent study on the 3′,5′‐dimethoxybenzoin photocage suggested that the photochemical pathway involving this cyclohexadienyl cation structure played only a minor role and a faster process could be the predominant pathway 52. Due to the limitations of our equipment, we were not able to observe any other intermediates prior to generating the proposed cyclohexadienyl cation structure ( A ).…”
Section: Methodsmentioning
confidence: 78%
“…The initial ultrafast bleach of the parent carbonyl at 1753 cm −1 (Figure 4D) further suggests that the carbonyl is involved in a transient interaction with the tetrazine ring that quickly removes that carbonyl double bond absorption out of the spectral range, akin to the processes of ring formation observed in dimethoxybenzoin photochemistry. [4244] The vibrational frequency shifts of the ester carbonyl are not seen, only the populations of the initial and recovered states are observed. Another possible interpretation is that the new CO absorption band of the intermediate state might be anomalously wide and comparable with the noise.…”
Section: Discussionmentioning
confidence: 99%
“…Phillips and his coworkers recently confirmed this observation and established the dominant reaction pathway. [16][17][18] The presence of a stereogenic center in a PPG is generally considered a disadvantage. A pair of enantiomers of the benzoin group creates a mixture of diastereomers when the leaving group is chiral.…”
Section: Introductionmentioning
confidence: 99%